Dampak Inkuiri Berjenjang terhadap Dimensi Literasi Sains Calon Guru Biologi - Riezky Maya Probosari; Sajidan Sajidan; Suranto Suranto; Baskoro Adi Prayitno (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2016)
This study examined how students’ scientific literacy changed over as they participated in hierarchy of inquiry learning. The hierarchy of inquiry  is a comprehensive approach in which students  working for an extended period of time that integrated several ways of inquiry systematically to investigate and respond to a complex question, problem, or challenge.  This  action research was  conducted in Biology Teacher Education Program Faculty of Teacher Training and Education Sebelas Maret University.  The students, who were at the 4rd semester and who studied the class of Plant Embriology, were purposely selected.   The data were collected from interviews with researchers, classroom observations, and collection of student portfolios. Student learning gains were measured using  academic writing assessment. which measured students’ ability in nominal literacy,  functional literacy,  conceptual literacy, and  multi-dimensional literacy.  The results showed that the scientific literacy  level increased on the last inquiry activities. It was suggested that hierarchy of inquiry could have a positive impact on students’ scientific literacy which drawn in their writing projects. Students who experienced the hierarchy of inquiry  emphasized the sentences reflecting the application and used high cognitive level sentences.  The findings can be helpful in the process of designing the best new curricula for teacher candidates in order to foster scientific literacy.Keywords:        scientific literacy, hierarchy of inquiry, cognitive level